1990
DOI: 10.1084/jem.172.6.1643
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function relationships among highly diverse T cells that recognize a determinant from influenza virus hemagglutinin.

Abstract: SummaryWe have analyzed the structural and genetic basis for T cell recognition of the complex formed between antigen and class II products of the major histocompatibility complex by performing sequence analysis of T cell receptors (TCRs) induced in response to the helper T cell site 1 of the influenza virus hemagglutinin . The results demonstrate, first, that structurally highly diverse TCRs can be utilized in recognition of the same antigen/1-Ed complex: 12 of 13 TCRs utilize unique Vct/VS gene segment combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 38 publications
(50 reference statements)
1
30
0
Order By: Relevance
“…Previously, it was observed that the repertoire of CTL directed against the MAGE-1 161-169 antigenic tumor peptide (HLA-A*0101) in a melanoma patient can be diverse in terms of both antigen recognition and TCR usage (Romero et al, 1995). Analyses of TCR repertoires specific for a variety of antigenic peptides presented in MHC class-I molecules have shown that they can be either relatively homogeneous (Kalams et al, 1994;Lehner et al, 1995) or highly diverse (Taylor et al, 1990;Cole et al, 1994). Thus far it is not clear what determines the degree of diversity in the TCR repertoires.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was observed that the repertoire of CTL directed against the MAGE-1 161-169 antigenic tumor peptide (HLA-A*0101) in a melanoma patient can be diverse in terms of both antigen recognition and TCR usage (Romero et al, 1995). Analyses of TCR repertoires specific for a variety of antigenic peptides presented in MHC class-I molecules have shown that they can be either relatively homogeneous (Kalams et al, 1994;Lehner et al, 1995) or highly diverse (Taylor et al, 1990;Cole et al, 1994). Thus far it is not clear what determines the degree of diversity in the TCR repertoires.…”
Section: Discussionmentioning
confidence: 99%
“…The TCR ␣-and ␤-chain genes cloned to generate TS1 mice were derived from a T cell line specific for the immunodominant epitope of influenza A virus PR8 hemagglutinin (HA) 3 (22,23). As a result, TS1 mice possess a high percentage of T cells specific for the hemagglutinin molecule S1 determinant (aa 110 -119) presented in the context of MHC class II IE d .…”
mentioning
confidence: 99%
“…The reaction was incubated at 25 °C for 3 min and stopped by the addition of an equal volume of 5 mM ethylenediaminetetraacetate (EDTA; pH 8.0) and extraction with phenol. The reaction products were precipitated twice with ethanol and converted to dsDNA for amplification in the PCR as described (Taylor et al 1990). Sequence analysis of the V~ gene segment from the SJL-HE-1.1 T-cell hybrid required that the V first be cloned into XZap (Stratagene, La Jolla, CA) in order to eliminate the BW5147 fusion partner V~ transcripts.…”
Section: Methodsmentioning
confidence: 99%
“…Sequence analysis of the V gene segment from the T2.5-5 T-cell clone was performed essentially as previously described (Taylor et al 1990). Constant region specific primers were used to direct one-sided amplification in the polymerase chain reaction (PCR) and the DNA amplification products were subjected to direct sequence analysis.…”
Section: Methodsmentioning
confidence: 99%